Perspectivas pedagógico-musicais para o ensino da viola no Brasil - Meirelles, Camila Torres (2018)
The instrumental teaching as a research field has increased in the last few years. However, musical instruments such as the viola have not followed this process if we consider the Brazilian national literature. From this scenario, this dissertation presents results from an instrumental teaching research, more specifically related to the viola. The research includes three important Brazilian professors from the following public universities: State University of Campinas, Federal University of Paraíba and Federal University of Rio Grande do Sul. The general objective is to verify actual viola teaching conceptions, contents and methodologies from classes of those three professors and how these practices have resulted in the violists learning process. The methodology consists in a qualitative approach, and the main instruments of data collecting were the bibliographical and documental research, observations and semi structured interviews. Considering that the viola teaching practices are based on many didactic materials and methodological procedures originally thought for the violin, the research showed that the expertise of the professors are essential to fulfill viola specific aspects that are not contemplated by these materials. After the observations it was possible to identify many pedagogical perspectives, technical and musical aspects that, aligned with the literature, consist in some of the main procedures that characterize the viola teaching nowadays.